Efektivitas Penggunaan Aplikasi Z-Pro Dalam Meningkatkan Efisiensi Pelayanan Zakat Di Lembaga Amil Zakat Persada - Setyo, Wahyu; Dikuraisyin, Basar (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2024)
This studio quickly checked that the Z-PRO application was very effective in improving the efficiency of zakat services at LAZ Persada. Previously, LAZ Persada used an inefficient manual method, limiting productivity and precision in service. The Z-PRO application is designed to automate various operational processes, such as managing donation data, the zakat distribution section, and information to investors in real time, to the top of transparency and submission of institutional reports. Using a descriptive investigation method, you will copy data through interviews, personal observations, and LAZ Persada's direction. The results of the study show that the implementation of Z-PRO has a significant positive impact, increasing employee productivity, reducing administrative errors and accelerating services to donations and beneficiaries. The implementation of this application has proven effective in generating public trust and improving the quality of zakat services, and therefore we recommend digitalization standards for other zakat institutions to maximize community business.